Earned Income and American Museums: The Perils of Privatization - Mulcahy, Kevin (Culture and Local Governance / Culture et gouvernance locale, 2019)
The basis of the American approach to culture eschews any collective state intervention. Cultural institutions, such as museums, originated as the beneficiaries of private donors. Such philanthropy benefits from a tax code that provides financial incentives for contributions to private organizations. For institutions, funds raised from ancillary activities, such as gift shops, also enjoy significant tax exemptions. Yet, despite these publicly financed tax deductions, cultural visions are privately conceived, and reflect the agendas of the donors. This attitude represents the basic principle of the American patronage system: one that is facilitated by a tax policy, not a cultural policy.